2007
DOI: 10.1159/000106397
|View full text |Cite
|
Sign up to set email alerts
|

Chiari Malformation Type III Treated with Primary Closure

Abstract: Chiari malformations represent various clinical and anatomic processes that entail varying degrees of involvement of the rhombencephalon (hindbrain). The type III Chiari malformation is distinctly rare. Chiari described only one case of his type III deformity, which is indicative of its rarity. We report a case of Chiari malformation type III, a female child who presented to us at the age of 1 month with a swelling at the back of the neck since birth. MRI revealed a Chiari type III malformation with a high cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
1
20
1
Order By: Relevance
“…Although we could not find any statistical data, we believe that a high number of births with neural tube defects give rise to an increase in CM III in our country. There was also a male predominance, as in the literature [6, 7, 13, 14, 19]. Most of our patients were newborns.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Although we could not find any statistical data, we believe that a high number of births with neural tube defects give rise to an increase in CM III in our country. There was also a male predominance, as in the literature [6, 7, 13, 14, 19]. Most of our patients were newborns.…”
Section: Discussionsupporting
confidence: 73%
“…Aribal et al [11] and Çakırer [18] each reported 2 cases. Other papers describe only 1 case each [7,8,9,10,12,13,14,15,16,17, 19, 20]. The percentage of CM III versus all Chiari malformations (4.4%) in our series is higher than in the literature (0.6–4%) [5,6,7,8].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations